2017
DOI: 10.18632/oncotarget.15377
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitroandin vivoeffects of nuclear and cytosolic parafibromin expression on the aggressive phenotypes of colorectal cancer cells: a search of potential gene therapy target

Abstract: Down-regulated parafibromin is positively linked to the pathogenesis of parathyroid, lung, breast, ovarian, gastric and colorectal cancers. Here, we found that wild-type (WT) parafibromin overexpression suppressed proliferation, tumor growth, induced cell cycle arrest and apoptosis in colorectal cancer cells (p<0.05), but it was the converse for mutant-type (MT, mutation in nucleus localization sequence) parafibromin (p<0.05). Both WT and MT transfectants inhibited migration and invasion, and caused better dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…However, Shen et al [ 17 ] found parafibromin expression was inversely associated with the differentiation of ovarian cancers. Recently, we reported that CDC73 expression was higher in moderately- than well-differentiated adenocarcinoma at both mRNA and protein level [ 29 ], opposite to our finding. As a differentiation marker, ALP activity was increased in CDC73 transfectants of colorectal cancer cells [ 13 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, Shen et al [ 17 ] found parafibromin expression was inversely associated with the differentiation of ovarian cancers. Recently, we reported that CDC73 expression was higher in moderately- than well-differentiated adenocarcinoma at both mRNA and protein level [ 29 ], opposite to our finding. As a differentiation marker, ALP activity was increased in CDC73 transfectants of colorectal cancer cells [ 13 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, we reported that CDC73 expression was higher in moderately- than well-differentiated adenocarcinoma at both mRNA and protein level [ 29 ], opposite to our finding. As a differentiation marker, ALP activity was increased in CDC73 transfectants of colorectal cancer cells [ 13 , 29 ]. Taken together, we concluded that CDC73 mRNA underlay the molecular mechanisms of the differentiation of gastric cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previously, we determined the parafibromin profiles and their clinicopathological significances in head and neck, lung, gastric, colorectal, and ovarian cancers. The downregulated expression of parafibromin in the above-mentioned cancers was negatively correlated with their aggressive variables and adverse prognosis ( Zheng et al, 2011 ; Shen et al, 2016 ; Zhu et al, 2016 ; Zheng et al, 2017a ; Zheng et al, 2017b ). In breast cancer, parafibromin expression was inversely correlated with T stage, clinicopathological stage, local lymphovascular invasion, and C-erbB2 expression ( Selvarajan et al, 2008 ).…”
Section: Introductionmentioning
confidence: 98%
“…Han et al 9 found that inhibiting the expression of transcription factor sp1 can promote the apoptosis of CRC cells and the arrest of cell cycle, thereby inhibiting the proliferation of CRC. Zheng et al 10 found that the overexpression of parafibromin (the cell division cycle protein) can inhibit the progression of CRC division. Chen et al 11 found that the over-expressed ribosomal protein S15A can induce malignant transformation of CRC cells through the p53 signaling pathway, consequently resulting in erroneous regulation of the p53 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%